1991
DOI: 10.1136/jcp.44.11.909
|View full text |Cite
|
Sign up to set email alerts
|

Central pontine myelinolysis in liver transplantation.

Abstract: Gross external findings were determined at necropsy and the brains then fixed whole by suspension in 10% formalin for three to six weeks before slicing. In the 47 cases collected prospectively the brain stem and cerebellum were detached and the cerebrum sliced coronally at one cm intervals. Any grossly obvious lesions were sampled for histological examination. Routinely, blocks were also taken from frontal, temporal, parietal and occipital lobes, hippocampus, basal ganglia, thalamus, cerebellum and medulla. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 38 publications
1
30
1
2
Order By: Relevance
“…Una serie de 50 pacientes fallecidos posterior a THO fueron sometidos a estudio neuropatológico, cinco tenían MP que no fue diagnosticada previamente 39 . No se observó una correlación directa entre cambios bruscos de la concentración de sodio plasmático y la aparición de MP 39 .…”
Section: N V E S T I G a C I ó Nunclassified
See 1 more Smart Citation
“…Una serie de 50 pacientes fallecidos posterior a THO fueron sometidos a estudio neuropatológico, cinco tenían MP que no fue diagnosticada previamente 39 . No se observó una correlación directa entre cambios bruscos de la concentración de sodio plasmático y la aparición de MP 39 .…”
Section: N V E S T I G a C I ó Nunclassified
“…No se observó una correlación directa entre cambios bruscos de la concentración de sodio plasmático y la aparición de MP 39 . Yu et al comunicaron una incidencia de MP de 3,5%, encontrando en algunos casos una hiponatremia previa al THO 40 .…”
Section: N V E S T I G a C I ó Nunclassified
“…9,20 One study found patients with a pre-operative SNa 5130 mmol/L were more likely to undergo a rapid intra-operative increases in SNa. 27 Boon et al 28 described five cases of previously undiagnosed myelinolysis among 50 post-mortem examinations of patients who died following LTx. Four of these patients had a rapid peri-operative increase in SNa, of whom three had a pre-operative SNa 5133 mmol/L.…”
Section: Interpretation and Context With Prior Literaturementioning
confidence: 99%
“…Some evidence suggests that cyclosporine, an immunosuppressive agent, may be causally related in transplant patients with CPM [11,12]. Liver transplant patients also account for the vast majority of childhood cases of CPM, for which no causal explanation has been supported thus far [13]. Hence, dysregulation of sodium ion metabolism and concomitant neurotoxicity of brain cells within the central pons appears to play a key role in most hypothesizing about the etiology of this disorder.…”
Section: Introductionmentioning
confidence: 99%